THE TRANSCENDENTAL AESTHETIC: WALT WHITMAN’S POETIC PHILOSOPHY - Choudhury, Madhusmita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Whitman’s poetry appears to portray transcendental ideals challenging the notion of a unified self. Subverting the conventional ideals of nature, he tends to portray the interconnection between nature, spirituality and individualism. The spiritual significance of nature is embodied in his poems which embraces the divine in nature. Again, he complicates the idea of a unified self, reflecting the complexities between individualism and collectivism which further unfurls the tensions of American identity. The complexities of human experience get intertwined with the interconnectedness of the significance of nature and the vision of a harmonious universe and inclusive possibility. Nature is explored as a source of spiritual guidance which facilitates the poet to draw a deeper connection with the universe. The paper explores the transcendental ideals of Walt Whitman exploring some of his poems.